The influence of education, credit access, and entrepreneurship on community welfare in Buleleng Regency - Diputra, Gde Indra Surya; Yoga, Gede Agus Dian Maha (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2025)
This study aims to examine the influence of education, credit access, and entrepreneurship on the level of community welfare in Buleleng Regency. The research seeks to provide evidence-based recommendations for more effective regional development policies. A quantitative associative approach was employed using primary data collected through questionnaires and secondary data from relevant institutions. Data analysis was conducted using SPSS and SmartPLS software, involving validity and reliability tests, structural model evaluation, and hypothesis testing. Significance was assessed using t-statistics (>1.96) and p-values (<0.05). The results reveal that both education and entrepreneurship have a significant positive effect on community welfare, with entrepreneurship emerging as the most influential factor. In contrast, access to credit was found to have a negative effect, indicating the need for improved financial literacy and credit management among the population. This study contributes to the limited body of literature that simultaneously examines education, credit access, and entrepreneurship in relation to community welfare in rural areas. It offers a comprehensive framework for policymakers to integrate educational development, entrepreneurial support, and prudent credit governance to enhance sustainable socio-economic outcomes